MP1 AND MAIA FUNDUS PERIMETRY IN HEALTHY SUBJECTS AND PATIENTS AFFECTED BY RETINAL DYSTROPHIES. Issue 8 (August 2015) - Parodi, Maurizio Battaglia; Triolo, Giacinto; Morales, Marco; Borrelli, Enrico; Cicinelli, Maria V.; Cascavilla, Maria L.; Bandello, Francesco
Abstract : Purpose: To compare retinal sensitivity obtained with MP1 and MAIA microperimeters in patients affected by retinal dystrophies (RD) and in healthy subjects. Methods: Thirty-six patients affected by RD and 25 healthy subjects were considered for the study. All patients and controls underwent a complete ophthalmic examination including fundus-related perimetry, performed by means of two microperimeters, the MP1 (Nidek Technologies) and the MAIA (CenterVue). Main outcome of the study was the comparison of retinal sensitivity. Such comparison was performed converting the MP1 decibel (dB) values to their MAIA equivalent dB values. Results: Mean retinal sensitivity in patients affected by RD was 5.68 ± 6.08 dB (mean ± SD) on MP1 (9.66 ± 10.06 dB converted to their equivalent MAIA values) and 14.66 ± 9.37 dB on MAIA ( P < 0.0001). Mean retinal sensitivity in healthy subjects was 18.46 ± 3.10 dB on MP1 (22.44 ± 7.08 dB on their converted equivalent MAIA values) and 28.52 ± 1.12 dB on MAIA ( P < 0.0001). Thirty eyes affected by RD (41%) showed retinal areas characterized by sensitivity under 1 dB on MP1, whereas the MAIA examination of the same areas revealed a mean retinal sensitivity of 4.7 dB. Moreover, 28 of these eyes disclosed also areas of absolute scotoma on MP1, but examining the same areas on MAIA, just 13 of these eyes (46%) disclosed an absolute scotoma. In addition, in a subgroup of 6 eyes affected by RD (8%) showing a retinal sensitivity of 20 dB on MP1, the corresponding value on MAIA varied from 26.3 dB to 30.0 dB, with a mean value of 27.8 ± 1.3 dB. Conclusion: The MAIA microperimeter provides a more accurate characterization of functional impairment in RD with respect to the MP1 system, especially in cases with low and high retinal sensitivity. MAIA microperimeter could reveal particularly useful in precisely identifying and monitoring subtle changes in retinal sensitivity, especially in view of the availability of therapies aiming at a functional rescue in patients with RD. Abstract : The comparison between MP1 and MAIA microperimetry reveals that MAIA microperimeter provides a more accurate characterization of functional impairment, especially in cases with low and high retinal sensitivity.